The Birth of Economic Thought and Specialized Economic Press among the Bulgarians in the Ottoman Empire in the XIX Century (A Mediterranean Perspective) - Nenovski, Nikolai; Penchev, Pencho (Research Papers, 2014)
The study presents and analyses the major features of the Bulgarian economic thought at its inception in the 1850s through to Bulgaria’s Liberation from Ottoman rule in 1878. The authors examine the main intellectual figures and the publication endeavours of specialised economic periodicals in the same period and discuss their specific features highlighting the fact that articles on theoretical issues make their way through slowly and with difficulties even when popularisation is their aim. The authors’ main thesis is that the Bulgarian economic thought, at the point of its formation, was characterized by three basic features: liberalism, nationalism and ethical approach to economic problems. Finally, we should note two other basic features of economic thinking from that period in Mediterranean Europe and the Ottoman Empire which also had a Bulgarian dimension, i.e. the vivid and explicit presence of eclecticism in both the theoretical and the methodological aspect and the primary role of the French economists and the French economic thought. The last part of the paper makes an attempt to sum up and put the early Bulgarian economic thought and specialised economic periodicals into comparative Mediterranean and Balkan perspective. This allows an adequate analysis and adds to the knowledge about the spread and influence of economic ideas.
Keywords: Economic thought; Bulgaria; Liberation; Nationalism; Ethics; Liberalism